In-situ Measurements Of Sorption Parameters With A Field And Laboratory Emission Cell (FLEC): A Comparison To The Test Emission Chamber Method - Rizk, M; Verriele, M; Mendez, M; Dusanter, S; Schoemaecker, C; Le Calve, S; Locoge, N (WIT Transactions on Ecology and the Environment, 2015)
A new method has been developed to measure sorption parameters on indoor surfaces on the field, based on the coupling of a Field and Laboratory Emission Cell (FLEC) and a Proton Transfer Reaction - Mass Spectrometer (PTR-MS). In this work, the method used for field applications is compared to the conventional method (used for laboratory scale experiment only) based on a 50-liter glass chamber (CLIMPAQ) coupled to an on-line GC analyser. The sorption of ethyl benzene on an unpainted gypsum board (exposed to a BTEX mixture) is presented. The CLIMPAQ experiment takes 13 times (160 hours) more than a FLEC experiment (12 hours). In addition, the FLEC walls do not present any sorption effect on internal walls while the CLIMPAQ shows important sink effect that can reach 45 + or - 2% of the total amount of injected concentration. The sorption parameters k sub(a) and kd were derived from the experimental concentration profiles using Tichenor's model and taking into account the walls sink effect for the CLIMPAQ. While the analysis of the FLEC data is very responsive to sorption parameters variation, the CLIMPAQ one leads to a large range of solutions for the same experimental profile. Therefore, the FLEC method is useful to measure accurately and within few hours sorption parameters in real indoor environments.